1964
DOI: 10.1002/bbpc.19640680115
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropie der Fluoreszenz und Phosphoreszenz. Naphthalin und einige Halogenderivate

Abstract: In Molekülen mit geeigneter Symmetrie gibt es eine lineare Beziehung zwischen dem Anisotropiegrad der Fluoreszenz und dem der Phosphoreszenz. Diese Beziehung ermöglicht die Bestimmung der relativen Anteile der Phosphoreszenzintensität mit verschiedenen Übergangsmomentrichtungen. In Naphthalin ist die Phosphoreszenz zu etwa 2/3 mit einem Übergangsmoment mit Richtung senkrecht zur Molekülebene gekoppelt. In den Halogennaphthalinen werden die Komponenten mit Übergangsmomentrichtung in der Molekülebene stark erhöh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

1965
1965
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…The experiments of McGlynn and co-workers (251, 252) have been alluded to above. The phosphorescence of naphthalene, phenanthrene, and other hydrocarbons is reduced both in intensity and lifetime in complexes with 1,3,5-trinitrobenzene and other acceptors (54,55,56,153,247). Christodouleas and McGlynn (42) have found that complexing with trinitrobenzene increases the value of the ISC ratio by factors of 30 and 75 for naphthalene and acenaphthene, respectively.…”
Section: Phosphorescence Polarization In Heterocyclic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments of McGlynn and co-workers (251, 252) have been alluded to above. The phosphorescence of naphthalene, phenanthrene, and other hydrocarbons is reduced both in intensity and lifetime in complexes with 1,3,5-trinitrobenzene and other acceptors (54,55,56,153,247). Christodouleas and McGlynn (42) have found that complexing with trinitrobenzene increases the value of the ISC ratio by factors of 30 and 75 for naphthalene and acenaphthene, respectively.…”
Section: Phosphorescence Polarization In Heterocyclic Compoundsmentioning
confidence: 99%
“…Recently, several workers (55,67,84,280,336) using the method of photoselection, have independently examined the changes in the polarization characteristics of the emission that accompany the changes in lifetime on halogen substitution. The study has recently been extended to absolute polarization measurements of these halonaphthalenes in biphenyl crystals (37a).…”
Section: Phosphorescence Polarization In Heterocyclic Compoundsmentioning
confidence: 99%
“…With excitation at 282 nm (∼35 500 cm –1 ), the fluorescence anisotropy of 3 varies significantly across the band between −0.09 at ∼31 400 cm –1 to a maximum of 0.16 at ∼31 000 cm –1 . Naphthalene also shows variation in the anisotropy of its fluorescence, which ranges from ∼0.08 to ∼0.16 with excitation at 313 nm (∼31 900 cm –1 ) . Polarized excitation spectra, observed at 318 nm (the fluorescence maximum at 77 K), revealed a steep drop in anisotropy between ∼32 300 and 33 300 cm –1 from 0 to −0.1 and a gradually increasing anisotropy from ∼33 300 to 37 000 cm –1 of −0.1 to ∼0.…”
Section: Resultsmentioning
confidence: 97%
“…5 we see that deuteration indeed causes a significant change in the polarization of the phosphorescence. From the change in the degree of polarization we can determine the influence of d-substitution on the in-plane-and on the out-of-plane polarized rate using the photoselection equation 14 . Since the different directions of polarization originate from the radiative decay of different triplet sublevels we can determine from the degree of polarization the influence of deuteration on the individual radiative rates from T z and T !/ or T* (see Fig.…”
Section: Resultsmentioning
confidence: 99%